Professional Android Open Accessory Programming with Arduino. - Goransson, Andreas (Programmer to programmer., 2012)
Chapter 5: Creating the Accessory Library; Getting Started with Android Libraries; Building the P2PMQTT Library; Preparing the Library Project; Sketching the API; Implementing MQTT; Decoding MQTT; Managing Open Accessory Connections; Creating the Connection Class; USB Connection; Bluetooth Connection; Creating the Connection; Summary; Chapter 6: Using Your Accessory Library; Using Custom Android Libraries; The WroxAccessories Library; Building the Mini Projects; The LSMSD; The Parking Assistant; The Basic Robot; The Sampler; Summary; Chapter 7: Digital Arduino; Digital Actuators.